Morphological Characterization of Cherry Rootstock Candidates Selected from Central and East Black Sea Regions in Turkey - Aysen Koc; Zumrut Celik; Mustafa Akbulut; Sukriye Bilgener; Sezai Ercisli; Mehmet Gunes; Resul Gercekcioglu; Ahmet Esitken (The Scientific World Journal)
The use of rootstocks particularly for sweet cherry cultivars is of great importance for successful and sustainable production. Choosing the right cherry rootstocks is just as important as choosing the right cultivar. In this study, 110 sweet cherry, 30 sour cherry, and 41 mahaleb types displaying rootstock potential for sweet cherry cultivars were selected from Central and East Black Sea Regions in Turkey. The morphologic characteristics of the studied genotypes were compared with the standard clonal rootstocks PHL-A, MaxMa 14, Montmorency, Weiroot 158, Gisela 5, Gisela 6, and SL 64. A total of 42 morphological UPOV characteristics were evaluated in the selected genotypes and clonal rootstocks. The obtained data were analyzed by using principal component analysis and it revealed that eigenvalues of the first 3 components were able to represent 36.43% of total variance. The most significant positive correlations of the plant vigor were determined with leaf blade length and petiole thickness. According to the diversity analysis of coefficients, the 05 C 002 and 08 C 039 genotypes were identified as being similar (6.66), while the 05 C 002 and 55 S 012 genotypes were determined as the most distant genotypes (325.84) in terms of morphology.